Design, Synthesis, and Biological Evaluation of Indole-2-carboxamides as Potential Multi-Target Antiproliferative Agents - Lamya H. Al-Wahaibi; Anber F. Mohammed; Mostafa H. Abdelrahman; Laurent Trembleau; Bahaa G. M. Youssif (MDPI AG, 2023)
A small set of indole-based derivatives, IV and Va-I, was designed and synthesized. Compounds Va-i demonstrated promising antiproliferative activity, with GI50 values ranging from 26 nM to 86 nM compared to erlotinib's 33 nM. The most potent antiproliferative derivatives-Va, Ve, Vf, Vg, and Vh-were tested for EGFR inhibitory activity. Compound Va demonstrated the highest inhibitory activity against EGFR with an IC50 value of 71 ± 06 nM, which is higher than the reference erlotinib (IC50 = 80 ± 05 nM). Compounds Va, Ve, Vf, Vg, and Vh were further tested for BRAFV600E inhibitory activity. The tested compounds inhibited BRAFV600E with IC50 values ranging from 77 nM to 107 nM compared to erlotinib's IC50 value of 60 nM. The inhibitory activity of compounds Va, Ve, Vf, Vg, and Vh against VEGFR-2 was also determined. Finally, in silico docking experiments attempted to investigate the binding mode of compounds within the active sites of EGFR, BRAFV600E, and VEGFR-2.